Digital Tourism Promotion Training to Enhance Local Community Capacity in a Tourism Village - Qorry Insany; Getar Hati (Global Writing Academica Researching and Publishing, 2025)
The growing reliance on digital platforms in tourism has reshaped how destinations communicate and compete, particularly for tourism villages that depend on community involvement. The strength of human resources in managing tourism potential and conducting effective promotion is a key determinant of tourism village development. Therefore, targeted training is necessary to enhance local community capacity in tourism management and digital promotion to expand wider visitors. This study examines digital tourism promotion training as a community development practice in Rindu Hati Tourism Village, Indonesia, focusing on collaboration between local tourism actors and Universitas Bengkulu (UNIB). This research employs a qualitative descriptive approach to explore processes, practices, and outcomes of digital tourism promotion training within the community. Data were collected through interviews, observation, and documentation, capturing how digital promotion was prepared, implemented through participatory training, and integrated into everyday tourism management. The findings show that digital tourism promotion developed through collective training activities that enabled the community to manage websites and digital video platforms as shared promotional spaces. Digital platforms functioned not only as marketing tools but also as media for expressing local identity and strengthening community participation. The collaboration with the local university supported learning and facilitation while maintaining community control over tourism narratives. Furthermore, this research found that this training contributes to local community development when embedded in participatory processes, educational collaboration, and locally grounded practices.